The Legal Implications of Business Agreements in the Digital Era: A Case Study on E-Commerce - Chairus Suriyat; Tina Muhardika Handayani; Junaidi Lubis (Outline Publisher, 2024)
The rapid growth of e-commerce has introduced numerous legal challenges that businesses must navigate to ensure the effectiveness and security of their digital transactions. This research examines the legal implications of business agreements in the digital era, focusing on the e-commerce sector. Key legal concerns addressed in the study include the enforceability of electronic contracts, data privacy compliance, intellectual property protection, consumer rights, and jurisdictional issues. Through a case study methodology, data was collected from industry experts, legal professionals, and businesses involved in e-commerce. The findings reveal that many e-commerce businesses struggle with ensuring the clarity and enforceability of electronic contracts, particularly in click-wrap and browse-wrap agreements. Additionally, data privacy regulations, such as the General Data Protection Regulation (GDPR), present significant compliance challenges, especially for businesses operating across multiple jurisdictions. Intellectual property protection is another critical issue, as businesses selling digital products face increased risks of piracy and unauthorized use. Furthermore, the study highlights the importance of consumer protection, emphasizing the role of transparency and clear return policies in minimizing legal disputes. In conclusion, the research suggests that e-commerce businesses must adopt proactive legal strategies, including better contract management and adherence to data protection laws, to mitigate risks and thrive in the digital marketplace.